2013
DOI: 10.3109/1061186x.2013.850502
|View full text |Cite
|
Sign up to set email alerts
|

Combined delivery of BCNU and VEGF siRNA using amphiphilic peptides for glioblastoma

Abstract: Combined delivery of chemical drug and therapeutic gene has been introduced as an efficient method for the treatment of cancers such as glioblastoma. In this study, bis-chloroethylnitrosourea (BCNU) and vascular endothelial growth factor (VEGF) small interfering RNA (VEGF-siRNA) were co-delivered into C6 glioblastoma cells using a non-toxic peptide-based carrier. The R3V6 peptides, which are composed of 3-arginine and 6-valine, formed self-assembled micelles in aqueous solution. BCNU, a hydrophobic anti-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Although these vectors can deliver DNA into the cells in vitro , they have high toxicity, limiting their in vivo application . To avoid high toxicity of the carriers, short amphiphilic peptide micelles were developed for gene delivery . The R7L10 amphiphilic peptide forms micelles in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these vectors can deliver DNA into the cells in vitro , they have high toxicity, limiting their in vivo application . To avoid high toxicity of the carriers, short amphiphilic peptide micelles were developed for gene delivery . The R7L10 amphiphilic peptide forms micelles in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 To avoid high toxicity of the carriers, short amphiphilic peptide micelles were developed for gene delivery. [12][13][14][15] The R7L10 amphiphilic peptide forms micelles in aqueous solution. R7L10 is composed of a 7-arginine stretch and a 10-leucine stretch.…”
Section: Introductionmentioning
confidence: 99%
“…Micellar nanodelivery systems for several drugs for the treatment of GBM have been developed and reviewed [5]. For instance, a micellar system based on amphiphilic peptides and incorporating bis-chloroethylnitrosourea (BCNU) and vascular endothelial growth factor (VEGF) small interfering RNA (VEGF-siRNA), was prepared and tested in C6 glioblastoma cells [6]. The micelles showed better delivery of BCNU into the cells and remarkably reduced expression of VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In vitro studies showed that BCNU-loaded R3V6 (R3V6-BCNU) more efficiently delivered siRNA or plasmid DNA (pDNA) than did empty R3V6 micelles. 10 Furthermore, the R3V6-BCNU/pDNA complex were more toxic to the cancer cells than was the mixture of BCNU and pDNA.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The improved delivery efficiency of plasmid DNA and siRNA may be due to the stabilization of the micelle structure by provision of stronger hydrophobic cores such as that in BCNU.…”
mentioning
confidence: 99%